A educação em marketing no Brasil: um olhar incursivo sob a lente da racionalização - Leal, Janayna Souto (2022)
The purpose of this thesis is to analyze the path of marketing education in Brazil, from its begining in 1954 to the present day, in the light of rationalization. This chronological incursion of the facts about the investigated phenomenon helped us build an argumentative base (and of understanding) to respond the following guiding question: considering both past and current paradigmatic, not to mention the methodological and professional provisions, how can be the future of marketing education in Brazil be construed? Based on this principle, we elaborated three research objectives that were distributed and structured in the five chapters of this work - introduction, studies, and final considerations. In the first study, we present the formation process of higher education in Administration in the 20th century, illuminated by the theoretical category of rationalization, with historiographical inspiration and analysis of the current literature. We identify in the paths traveled an administrative rationality based on the search for efficiency of managerial thinking, scrutinized from the standpoint of the professionalization of the administrator and the standardization of processes, especially after the importation of the American model. In the second one, the focus shifts specifically to the formative field of marketing. Then, we describe the constitutive formation of the discipline in Brazil and its rise in the interval from 1954 to 2000, based on rational thinking in which, through document analysis and in-depth interviews with six Brazilian academics active in the period under study, we observe that the trajectory of the development of marketing education in the country gained relevant contours, assuming a prominent role as an area of specialization of the Administration course, by printing a rational conduction in the decision-making processes allusive to its development. This analytical effort allowed us to enter the 21st century, more precisely in study three, in which we examined the course of academic education in the field of management and marketing in Brazil, in that century, through rational categories. With the survey of secondary sources and the analysis of the literature, we evidenced a mimetic direction in the use of a ‘quantified evaluation’, besides a standard behavior in the distribution of curricula in the country, reflecting a rational line of greater achievement in efficiency and productivity in the movements oriented to education in Administration and marketing. Therefore, as a consequence of the actions undertaken in this work, we consider that the knowledge taught and the academic practices (translated into menus, works, professors and exponents of the area) still remain faithful and profiled to the mimetic isomorphism. Yet, when thinking about the future of the marketing field, the invasion of a myriad of digital technology, aligned with the concept of marketing analytics, bring the most innovative and exciting opportunities for this educational area and, at the same time, offer its most central challenges as well.